(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Language plays an integral role in understanding the world view of each nation. However, the problem of analyzing the expression of the concept of "beauty" in language (in English, Uzbek national cultures) has not been studied from the point of view of cognitive linguistics and linguistic culturology. Therefore, the aesthetic landscape of the world in English and Uzbek languages, the possibilities of expressing and reflecting the concept of "beauty" in the phraseological and lexical layers of the language, the interpretation of values in different cultures, the comparative analysis of linguistics and cultural features, are directly related to cognitive linguistics, linguoculturalism, general linguistics, determines the relevance of related learning. This article deals with the cross analysis of lexical units related to the concept of beauty in English and Uzbek languages.